The Protection of Civilians in Peacekeeping Operations : A Legal Obligation - Morris, Tamer, (Human Rights and Humanitarian Law E-Books Online, Collection 2024., 2025)
While the Security Council has been mandating peacekeepers to protect civilians since 1999, there is still contention on its legal meaning. Even though the concept of 'protection' can seem self-evident, as the concept of 'protection' is borrowed language, each body of law will perceive 'protection' through a different lens. However, as the mandate creates a legal obligation on UN peace missions, a clear understanding of protection is fundamental to ensure performance and accountability.